AB0128 Total Calcium-Sensing Receptor Expression in Circulating Monocytes is Increased in Rheumatoid Arthritis Patients with Severe Coronary Artery Calcification. (10th June 2014) - Paccou, J.; Boudot, C.; Renard, C.; Liabeuf, S.; Kamel, S.; Fardellone, P.; Massy, Z.; Brazier, M.; Mentaverri, R.
Abstract : Background: Human circulating monocytes express the calcium-sensing receptor (CaSR) and are involved in atherosclerosis. Vascular calcification is commonly used as a subclinical marker of atherosclerosis and has been linked to increased all-cause mortality, cardiovascular mortality and coronary events. Moreover, patients with RA are known to develop early-onset, widespread calcification in various vascular beds. We have previously assessed CaSR expression by flow cytometry in human circulating monocytes and have provided evidence that this type of approach could be useful in certain clinical situations, in which changes in CaSR expression can be expected. Objectives: This study investigated the potential association between vascular calcification in rheumatoid arthritis (RA) and CaSR expression in circulating monocytes. Methods: In this cross-sectional study, 50 RA patients were compared to 25 control subjects matched for age and gender. Isolation of peripheral blood mononuclear cells and flow cytometry analysis were performed to study the surface and total CaSR expression in circulating monocytes. Coronary artery calcium (CAC) and abdominal aortic calcification (AAC) scores were evaluated by computed tomography and an association between these scores and the surface and/or total CaSR expression in circulating monocytes in RA patients was investigated. Results: The two groups were similar in terms of age (RA: 60.9±8.3 years, versus controls: 59.6±5.3 years) and gender (RA: 74.0% females versus 72.0% females). RA patients did not present a higher prevalence or a greater burden of CAC or AAC compared to age- and gender-matched controls. When compared with control subjects, RA patients did not exhibit greater total CaSR (101.6% ±28.8 vs. 99.9% ±22.0) or surface CaSR (104.6% ±20.4 vs. 99.9% ±13.7) expression, but total CaSR expression in circulating monocytes was significantly higher in RA patients with severe CAC (Agatston score ≥200, n=11) than in patients with mild-to-moderate CAC (1-199, n=21) (p=0.01). Conclusions: This study demonstrates, for the first time, that total CaSR expression in human circulating monocytes is increased in RA patients with severe coronary artery calcification. References: Paccou J, Brazier M, Mentaverri R, et al. Vascular calcification in rheumatoid arthritis: prevalence, pathophysiological aspects and potential targets. Atherosclerosis 2012;224:1418-23. Paccou J, Boudot C, Mary A, et al. Determination and modulation of total and surface calcium-sensing receptor expression in monocytes in vivo and in vitro. PLoS one 2013;8:e74800. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2377